Optimization of a Method to Detect Autoantigen-Specific T-Cell Responses in Type 1 Diabetes - Musthaffa, Yassmin; Nel, Hendrik J.; Ramnoruth, Nishta; Patel, Swati; Hamilton-Williams, Emma E.; Harris, Mark; Thomas, Ranjeny (Frontiers in Immunology, 2020)
The development of tolerising therapies aiming to inactivate autoreactive effector T-cells is a promising therapeutic approach to control undesired autoimmune responses in human diseases such as Type 1 Diabetes (T1D). A critical issue is a lack of sensitive and reproducible methods to analyse antigen-specific T-cell responses, despite various attempts. We refined a proliferation assay using the fluorescent dye 5,6-carboxylfluorescein diacetate succinimidyl ester (CFSE) to detect responding T-cells, highlighting the fundamental issues to be taken into consideration to monitor antigen-specific responses in patients with T1D. The critical elements that maximise detection of antigen-specific responses in T1D are standardisation of gating parameters, titration of CFSE concentration, selecting the optimal CFSE staining duration and the duration of T-cell stimulation. Optimisation of these elements enable robust, reproducible application to longitudinal cohort studies or clinical trial samples in which antigen-specific T-cell responses are relevant, and adaptation to other autoimmune diseases.